Enhanced cooporation in an enlarged EU - Joachim Ahrens; Renate Ohr; Götz Zeddies (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2006)
The paper adresses the need for more flexibility in the integration process of the European Union after its recent eastward enlargement. Due to the increasing number of decision-makers and the increasing heterogeneity of economic structures, financial constraints, societal preferences, and political interests, European integration based on the uniformity principle is hardly feasible. In order to avoid a rank growth of integration and yet to strengthen the momentum of flexibility, so-called enhanced cooperation appears to be an appropriate instrument to be applied to the overall integration process. In this context the paper analyzes different possible developments of selected common policies in the EU if enhanced cooperation is practised by a sub-group of EU-members. Based on cluster analysis similarities and distinctions among the EU members with respect to some specific policy realms are elaborated to identify clusters, or clubs, of countries which may apply the instrument of enhanced cooperation in the specific policy fields.
Keywords: E61; F15; F42; 330; european integration; enhanced cooperation; cluster analysis; Europäische Integration; Politische Entscheidung; Politisches System; Internationale Beziehungen; Clusteranalyse; EU-Staaten